PENERAPAN KOMUNIKASI TERAPEUTIK DALAM PENANGANAN PASIEN GANGGUAN JIWA DI RUMAH SAKIT JIWA PROVINSI BALI - TIRTAWATI, ANAK AGUNG RAI (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2017)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Therapeutic communication is one way that can be used to help the healing process of the patient. This research was conducted to see the implementation of therapeutic communication in handling mental disorder patient according to Standard Operational Procedure (SOP) at Bali Provincial Mental Hospital 2017. The formulation of the problem is